SUMO E3 Ligases GmSIZ1a and GmSIZ1b regulate vegetative growth in soybean1 . Issue 1 (January 2017) - Cai, Bin; Kong, Xiangxiong; Zhong, Chao; Sun, Suli; Zhou, Xiao Feng; Jin, Yin Hua; Wang, Youning; Li, Xia; Zhu, Zhendong; Jin, Jing Bo
Abstract: SIZ1 is a small ubiquitin‐related modifier (SUMO) E3 ligase that mediates post‐translational SUMO modification of target proteins and thereby regulates developmental processes and hormonal and environmental stress responses in Arabidopsis . However, the role of SUMO E3 ligases in crop plants is largely unknown. Here, we identified and characterized two Glycine max (soybean) SUMO E3 ligases, GmSIZ1a and GmSIZ1b . Expression of GmSIZ1a and GmSIZ1b was induced in response to salicylic acid (SA), heat, and dehydration treatment, but not in response to cold, abscisic acid (ABA), and NaCl treatment. Although GmSIZ1a was expressed at higher levels than GmSIZ1b, both genes encoded proteins with SUMO E3 ligase activity in vivo . Heterologous expression of GmSIZ1a or GmSIZ1b rescued the mutant phenotype of Arabidopsis siz1‐2, including dwarfism, constitutively activated expression of pathogen‐related genes, and ABA‐sensitive seed germination. Simultaneous downregulation of GmSIZ1a and GmSIZ1b ( GmSIZ1a/b ) using RNA interference (RNAi)‐mediated gene silencing decreased heat shock‐induced SUMO conjugation in soybean. Moreover, GmSIZ1RNAi plants exhibited reduced plant height and leaf size. However, unlike Arabidopsis siz1‐2 mutant plants, flowering time and SA levels were not significantly altered in GmSIZ1RNAi plants. Taken together, our results indicate that GmSIZ1a and GmSIZ1b mediate SUMO modification and positively regulate vegetative growth in soybean. Abstract : SUMOylation is a rapid and reversible post‐translational process, which affects protein‐protein interactions, protein targeting, enzymatic activity and protein stability. However, the role of SUMOylation in soybean is unknown. Here, we report that two soybean SUMO E3 ligases, GmSIZ1a and GmSIZ1b, mediate SUMO modifications and positively regulate vegetative growth in soybean.